2002
DOI: 10.1073/pnas.052005999
|View full text |Cite
|
Sign up to set email alerts
|

Network of coupled promoting motions in enzyme catalysis

Abstract: A network of coupled promoting motions in the enzyme dihydrofolate reductase is identified and characterized. The present identification is based on genomic analysis for sequence conservation, kinetic measurements of multiple mutations, and mixed quantum͞ classical molecular dynamics simulations of hydride transfer. The motions in this network span time scales of femtoseconds to milliseconds and are found on the exterior of the enzyme as well as in the active site. This type of network has broad implications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
595
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(644 citation statements)
references
References 29 publications
44
595
1
Order By: Relevance
“…(27,42,44). The majority (13) of this group of 20 is involved in H-bonds to other solvent, and half make apolar OOH-C contacts.…”
Section: Study Of D27⅐mtx Interactions At the Dhfr Active Site Using Ndmentioning
confidence: 99%
See 1 more Smart Citation
“…(27,42,44). The majority (13) of this group of 20 is involved in H-bonds to other solvent, and half make apolar OOH-C contacts.…”
Section: Study Of D27⅐mtx Interactions At the Dhfr Active Site Using Ndmentioning
confidence: 99%
“…It catalyzes the NADPH-dependent reduction of 7,8-dihydrofolate, producing 5,6,7,8-THF. DHFR has been extensively studied by NMR (11), site-directed mutagenesis (12), and molecular dynamics (13) to unravel the potential coupling of motion by distal residues to catalysis (14,15). In particular, a regulatory loop, the Met-20 loop (residues 9-24), has been observed to adopt open, closed, and occluded conformations by x-ray crystallography (16) and closed and occluded conformations by NMR (17,18).…”
mentioning
confidence: 99%
“…Such a concept is appealing because the energy landscape of enzymes even in the folded state is rugged [5], and hence thermal energy might be sufficient to access several conformational substates during a typical reaction cycle [2]. In recent years, results from a number of studies have been used to propose that dynamic motions in a network of residues that promote catalytically-relevant structural transitions may be encoded in the protein structure [6,7,8,9,10,11,12,13,14,15,16]. While it is difficult to unambiguously demonstrate whether collective dynamics involving a network of residues facilitates catalysis [17], it is clear that enzymes sample a number of distinct states during a reaction cycle.…”
Section: Introductionmentioning
confidence: 99%
“…While it is difficult to unambiguously demonstrate whether collective dynamics involving a network of residues facilitates catalysis [17], it is clear that enzymes sample a number of distinct states during a reaction cycle. In the best studied example of E. coli dihydrofolate reductase (DHFR) the role of the conformational motions in the enzyme in facilitating the hydride transfer has been linked using mutational studies [10,18,19], NMR relaxation dispersion measurements [20,21,22] that probe the dynamics on µs to ms time scale, molecular dynamics simulations [6,7,13], and sequence analysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] There is evidence that such a coupling of fast and slow dynamical modes may play a significant role in DNA polymerase mechanisms. Pioneering single molecule studies of polymerases replicating DNA stretched under differing tensions 28,29 showed that the replication rate is sensitive to forces exerted on the template strand.…”
Section: Introductionmentioning
confidence: 99%